POTENTIAL OF THE MODERN ACE INHIBITOR ZOFENOPRIL IN CLINICAL PRACTICE: CARDIOPROTECTIVE, ANTI-ISCHEMIC, AND ANTIATHEROGENIC EFFECTS - M. G. Bubnova (Кардиоваскулярная терапия и профилактика)
The review discusses various aspects of angiotensin-converting enzyme (ACE) inhibitor therapy in patients with cardiovascular disease (CVD), including acute myocardial infarction (AMI). The focus is on the modern ACE inhibitor zofenopril, its specific pharmacological characteristics, and additional cardioprotective, anti-ischemic, and antiatherogenic effects. The existing evidence of clinical effectiveness of zofenopril and its potential for a wider use in clinical practice are also addressed.